Western art and the wider world - Wood, Paul (Chichester, West Sussex : Wiley Blackwell, 2014)
Western Art and the Wider World explores the evolving relationship between the Western canon of art, as it has developed since the Renaissance, and the art and culture of the Islamic world, the Far East, Australasia, Africa and the Americas.-Explores the origins, influences, and evolving relationship between the Western canon of art as it has developed since the Renaissance and the art and culture of the Islamic world, the Far East, Australasia, Africa and the Americas -Makes the case for 'world art' long before the fashion of globalization -Charts connections between areas of study in art that long were considered in isolation, such as the Renaissance encounter with the Ottoman Empire, the influence of Japanese art on the 19th-century French avant-garde and of African art on early modernism, as well as debates about the relation of 'contemporary art' to the past.-Written by a well-known art historian and co-editor of the landmark Art in Theory volumes.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed December 10, 2013).
Keywords: Art -- History; ART -- History -- General; Art; Electronic books; History; Electronic books